Pengaruh Kualitas Pelayanan Dan Responsifitas Karyawan PT KAI Terhadap Kepuasan Pelanggan - Leisubun, Abdul Gani; Rismawati, Rismawati; Qoniatusholikha, Qoniatusholikha; Iklima, Faradila Nur; Sajidah, Alifah (CV. ITTC INDONESIA, 2025)
The current research investigates the influence of service quality and employee responsiveness on passenger satisfaction at PT KAI, the nation’s largest public-transport operator. In today’s fiercely competitive service landscape, the caliber of service delivered together with how swiftly and skillfully staff address customer needs and complaints shapes both satisfaction and long term loyalty. Adopting a quantitative design, the study surveyed passengers who had traveled with PT KAI at least twice in the preceding six months. The questionnaire drew on the SERVQUAL model, supplemented with items specific to responsiveness, and the data were examined via multiple-linear regression to test the joint and individual effects of the two predictors. Findings show that both variables significantly raise satisfaction, with service quality exerting the stronger influence. These results underscore the value of sharpening employees’ interpersonal skills especially communication, empathy, and conflict management through focused training programs to boost overall service excellence. Findings from this research are applicable both as a practical framework for enhancing public service delivery at PT KAI and as an academic resource for studies on consumer behavior in transportation